3-Aminopropyl-triethoxysilane-functionalized rice husk and rice husk ash reinforced polyamide 6/graphene oxide sustainable nanocomposites. (September 2017) - Allahbakhsh, Ahmad; Noei Khodabadi, Fereidoun; Hosseini, Fatemeh Sadat; Haghighi, Amir Hossein
Graphical abstract: Highlights: Functionalized-rice husk ash/polyamide6/graphene oxide nanocomposites are prepared. Surface functionalization of rice husk ash nanoparticles increases interfacial interactions. Sustainable rice husk ash-filled nanocomposites present enhanced properties. Abstract: Rice husk and rice husk ash are two well-known sustainable materials for wastewater purification applications. In this work, functionalized-rice husk and -rice husk ash reinforced polyamide 6/graphene oxide nanocomposites are fabricated using the solution casting method. 3-Aminopropyl-triethoxysilane is used as the functionalizing agent for the surface modification of rice husk and rice husk ash particles. Siloxane bonding between silanol groups of the functionalizing agent and silica containing particles can result in the introduction of amino groups on the surface of particles, which can react with either terminal carboxyl groups or amide groups of the polyamide 6. Functionalized-rice husk ash, which contains a large amount of nano silica, forms distributed nano-sized aggregates in the structure of the polyamide 6. Moreover, the simultaneous presence of graphene oxide and rice husk ash, as an organic/inorganic nano-system, in the matrix structure results in a clear enhancement in the structural and mechanical characteristics of final nanocomposites. This is the result of possible strong interactions between the polymeric matrix and the organic/inorganic nano-system. The influences of the organic/inorganic nano-system on the melting process, morphology and dynamic-mechanical properties of reinforced nanocomposites are investigated in details. Moreover, the impacts of the organic/inorganic nano-system loading on the thermal stability of fabricated nanocomposites are studied. Considering results presented here and the well-known adsorbent characteristics of rice husk ash nanoparticles, the functionalized-rice husk ash/graphene oxide/polyamide 6 sustainable nanocomposite is a perfect candidate for fabricating nanofibers, which are applicable in wastewater purification applications.